ASSOCIATION BETWEEN HEMOGLOBIN LEVEL AND BODY MASS INDEX IN THE FIRST TRIMESTER OF PREGNANCY WITH BIRTHWEIGHT IN TEMBALANG - Saniya Millatina; Nurul Setiyorini; Vannya Dewi Puspitasari; Ani Margawati (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Low birthweight babies (LBW) have a risk of death 10-20 times greater than normal birthweight babies. Data from Semarang Health Office in 2018, there were 24 cases of LBW in Tembalang. Low nutrional status, namely low body weight and anemia were the risk factor of LBW incident. Objective: To analyze the association features between hemoglobin levels and body mass index in the first trimester of pregnancy with LBW in Tembalang. Methods: This was a observational research with cross sectional analytic design. Respondents were mothers who met the criteria and randomly selected using simple random sampling. There were 44 respondents in this research. The independent variables are body mass index and hemoglobin levels in the first trimester with birthweight as dependent variables. Data is obtained from structured questionnaires and medical records or maternal KIA book. Chi-Square and logistic regression are used to analyze the data. Result: Respondents were mother, who did first trimester antenatal care at the Government's First Health Care Facility in the Tembalang. The majority are multiparity (56,8%), had normal midd-upper arm circumference (72,7%), had weight gain during pregnancy below recommendation (50%), had high compliance of blood vitamin consumption (68,2%), non-work status (59,1%), senior high school graduate (59,1%), and had good family income (52,3%). Analysis result showed there were no significant association between first trimester body mass index and birthweight (p=0,061), also between first trimester hemoglobin level and birthweight (p=1,000). Analysis from the two independent variables also showed no significat association with birthweight (p = 0,877). Conclusion: Most of the respondents had good nutritional status with hemoglobin level and body mass index features in the first trimester showed normal value. Average birthweight also in the normal value and the incidence of LBW is low. The research analyst showed no significant association between first trimester of body mass index and hemoglobin levels with birthweight.Keywords: Birthweight, Body Mass Index, Hemoglobin